The productivity slowdown in Canada: An ICT phenomenon? - Jeff Mollins; Pierre St-Amant (Bank of Canada, 2019)
We ask whether a weaker contribution of information and communication technologies (ICT) to productivity growth could account for the productivity slowdown observed in Canada since the early 2000s. To answer this question, we consider several methods capturing channels through which ICT could affect aggregate productivity growth. This includes an approach "à la Cette et al. (2015)" that focuses on the use of ICT capital. We also examine two-sector models including a simple approach with use and production effects, and an approach "à la Oulton (2012)" that highlights the role of relatively weak growth in ICT prices. However, Oulton's approach is based on strong assumptions about the structure of the economy, some of which are clearly inconsistent with Canadian data. We therefore propose a different model based on assumptions that are less restrictive but that still capture various channels (production, capital deepening, price effects). Our results indicate that ICT continues to contribute to productivity growth, but that this contribution has declined and accounts for part of the productivity slowdown. However, the slowdowns in productivity and in the contribution of ICT do not seem to have the same timing. While productivity slowed in the early 2000s, ICT contribution does not appear to have fallen until around the Great Recession. This prompts the conclusion that while ICT had little to no role in the initial productivity slowdown, it has been a major determinant of the subdued productivity growth since around the recession.
Keywords: D24; O4; O41; O47; 330; Productivity